Public Service Quality with Intervening Quality of Employee Performance at Policy Siaga 112 Probolinggo - Sutarjo Sutarjo; Nurul Jannah Lailatul Fitria (Inspektorat Kabupaten Majalengka, 2026)
Governance towards good governance requires quality Governance towards good governance requires quality policies, quality services, and quality employee performance. This is of interest to research related to the effect of policy quality on service quality through intervening employee performance quality related to the Probolinggo Siaga 112 City program in handling emergency conditions. Research with a descriptive quantitative approach examines the causal relationship between the variables of policy quality, service quality, and employee performance quality. Data was collected from questionnaire techniques on 100 people who met the criteria. The test results explain that Policy Quality is proven to significantly influence the Quality of Employee Performance directly; Quality of Employee Performance is proven to significantly influence Service Quality directly; and Policy Quality is proven to significantly influence Service Quality directly. And there is an indirect effect, namely the Quality of Employee Performance is proven to be intervening in influencing the Quality of Policy on Service Quality.